Investigation of Hepatitis B virus entry mechanism - Raymond, Chidinma (2022)
Hepatitis B infection is a global public health challenge that attacks the liver, resulting in severe hepatic and non-hepatic complications, particularly liver cirrhosis and hepatocellular carcinoma. This infection caused by the Hepatitis B virus (HBV) is the cause of the world's most common liver infection and the second leading cause of cancer worldwide. HBV is known to have a complicated replication cycle in which it utilises a reverse transcriptase with proofreading inability. The overlapping nature of the HBV genome, in addition to the proofreading inability of the HBV polymerase, culminates in high mutation rates with pleiotropic effects on both the polymerase and the surface genes. Mutations in the surface gene (HBsAg) have been linked to several clinical implications, such as vaccine escape and failure of HBV diagnostic assays. We hypothesised that the HBsAg variability would go beyond immune escape mutants, potentially extending to its interaction with cell receptors and entry. Therefore, in this study, we have studied the effect of HBsAg mutations on HBsAg interactions with cell receptors and on HBV entry using the pseudotyping system.